Placement on COVID-19 Units Does Not Increase Seroconversion Rate of Pediatric Graduate Medical Residents - Crisci, Timothy; Arregui, Samuel; Canas, Jorge; Hooks, Jenaya; Chan, Melvin; Powers, Cory; Schwaderer, Andrew L.; Hains, David S.; Starr, Michelle C. (Frontiers in Pediatrics, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated disease COVID-19 has presented graduate medical education (GME) training programs with a unique set of challenges. One of the most pressing is how should hospital systems that rely on graduate medical residents provide appropriate care for patients while protecting trainees. Objective: This cross-sectional study sought to assess the impact of hospital COVID-19 patient placement on pediatric graduate medical residents by comparing rates of SARS-CoV-2 seroconversion rates of residents that worked on designated COVID-19 teams and those that did not. Methods: Forty-four pediatric and medicine-pediatric residents at Riley Children’s Hospital (Indianapolis, IN) were tested for SARS-CoV-2 IgM and IgG seroconversion in May 2020 using enzyme-linked immunosorbent assays (ELISA, Abnova Catalog #: KA5826). These residents were divided into two groups: those residents that worked on designated COVID-19 teams, and those that did not. Results: 44/104 eligible residents participated in this study. Despite high rates of seroconversion, there was no difference in the risk of SARS-CoV-2 seroconversion between residents that worked on designated COVID-19 teams (26% or 8/31) and those that did not (31% or 4/13). Eleven of 44 residents (25%) tested positive for SARS-CoV-2 IgG, while only 5/44 (11.4%) tested positive for SARS-CoV-2 IgM. Conclusion: We did not observe a difference in SARS-CoV-2 seroconversion between different exposure groups. These data are consistent with growing evidence supporting the efficacy of personal protective equipment. Further population-based research on the role of children in transmitting the SARS-CoV-2 virus is needed.